Advanced Techniques for MRI of Atherosclerotic Plaque - Kerwin, William S. (2009)
This review examines the state of the art in vessel wall imaging by MRI with an emphasis on the biomechanical assessment of atherosclerotic plaque. Three areas of advanced techniques are discussed. First, alternative contrast mechanisms, including susceptibility, magnetization transfer, diffusion and perfusion, are presented in regards to how they facilitate accurate determination of plaque constituents underlying biomechanics. Second, imaging technologies, including hardware and sequences, are reviewed in regards to how they provide the resolution and SNR necessary for determining plaque structure. Finally, techniques for combining MRI data into an overall assessment of plaque biomechanical properties, including wall shear stress and internal plaque strain, are presented. The paper closes with a discussion of the extent to which these techniques have been applied to different arteries commonly targeted by vessel wall MRI.